Pathology of the liver in obese and diabetic ob/ob and db/db mice fed a standard or high-calorie diet - Nasser, Selim (2011)
Non-alcoholic fatty liver disease (NAFLD) is one of the commonest liver diseases in Western countries. Although leptin deficient ob/ob and db/db mice are frequently used as murine models of NAFLD, an exhaustive characterization of their hepatic lesions has not been reported to date, particularly under calorie overconsumption. Thus, liver lesions were characterized in 78 ob/ob and db/db mice fed either a standard or high-calorie (HC) diet, for one or three months. Steatosis, necroinflammation, apoptosis and fibrosis were assessed and the NAFLD activity score (NAS) was calculated. Steatosis was milder in db/db mice compared to ob/ob mice and was more frequently microvesicular. Although necroinflammation was usually mild in both genotypes, it was aggravated in db/db mice after one month of calorie overconsumption. Apoptosis was observed in db/db mice whereas it was only detected in ob/ob mice after HC feeding. Increased apoptosis was frequently associated with microvesicular steatosis. In db/db mice fed the HC diet for three months, fibrosis was aggravated while steatosis, necroinflammation and apoptosis tended to alleviate. This was associated with increased plasma β-hydroxybutyrate suggesting an adaptive stimulation of hepatic mitochondrial fatty acid oxidation (FAO). Nevertheless, one-third of these db/db mice had steatohepatitis (NAS ≥ 5), whereas none of the ob/ob mice developed non-alcoholic steatohepatitis under the same conditions. Steatosis, necroinflammation, apoptosis and fibrosis are modulated by calorie overconsumption in the context of leptin deficiency. Association between apoptosis and microvesicular steatosis in obese mice suggests common mitochondrial abnormalities. Enhanced hepatic FAO in db/db mice is associated with fibrosis aggravation.